Convergence and divergence in Diana monkey vocalizations - Candiotti, Agnès; Zuberbühler, Klaus; Lemasson, Alban (My University, 2012)
Individually distinct vocalizations are widespread among social animals, presumably caused by variation in vocal tract anatomy. A less-explored source of individual variation is due to learned movement patterns of the vocal tract, which can lead to vocal convergence or divergence in social groups. We studied patterns of acoustic similarity in a social call produced by 14 female Diana monkeys (Cercopithecus diana) in two free-ranging groups. Calls showed variability in fundamental frequency contours owing to individual identity and external context. Vocal divergence increased significantly between females during poor visibility and tended to increase in the presence of neighbours. In contrast, vocal convergence increased significantly between females during vocal interactions, because females matched the frequency contour of their own call with another females preceding call. Our findings demonstrate that these primates have some control over the acoustic fine structure of their most important social vocalization. Vocal convergence and divergence are two opposing processes that enable callers to ensure spatial proximity and social cohesion with other group members.
Keywords: vocal flexibility; individual signatures; call matching; non-human primates